2022
DOI: 10.1101/2022.03.18.484931
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AlphaFold encodes the principles to identify high affinity peptide binders

Abstract: Machine learning has revolutionized structural biology by solving the problem of predicting structures from sequence information. The community is pushing the limits of interpretability and application of these algorithms beyond their original objective. Already, AlphaFold's ability to predict bound conformations for complexes has surpassed the performance of docking methods, especially for protein-peptide binding. A key question is the ability of these methods to differentiate binding affinities between sever… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 21 publications
(24 reference statements)
1
24
0
Order By: Relevance
“…A recent study reported that competitive binding can be simulated in protein–peptide docking using ColabFold [ 48 ]. In other words, competition binding experiments of peptides can be performed virtually.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that competitive binding can be simulated in protein–peptide docking using ColabFold [ 48 ]. In other words, competition binding experiments of peptides can be performed virtually.…”
Section: Discussionmentioning
confidence: 99%
“…This method was based on previously published paper [48]. Modeling was performed in the publicly available localcolabfold (https://github.com/YoshitakaMo/localcolabfold (accessed on 29 June 2022)).…”
Section: Competitive Peptide Binding Predictions Using Alphafoldmentioning
confidence: 99%
“…Recently, it was reported that competitive binding can be simulated in protein–peptide docking using ColabFold [53]. In other words, it is possible to perform virtual competition binding experiments of peptides.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ability to design sequences with high solubility and high binding affinity that could be candidates for PPI inhibition from among a large number of candidate sequences is meaningful from both the drug discovery and industrial perspectives. Recently, it was reported that competitive binding can be simulated in protein-peptide docking using ColabFold [53]. In other words, it is possible to perform virtual competition binding experiments of peptides.…”
Section: Discussionmentioning
confidence: 99%
“…We reasoned that the recent advances in protein structure prediction could help overcome both limitations: that of structure based methods in utilizing large amounts of known binding data, and sequence-based methods, in using structural information. AlphaFold (9) and RoseTTAFold (10) predict highly accurate structures (11) and structure quality confidence metrics that have been used to distinguish pairs of proteins which bind from those that don’t with some success (12, 13). However, while these methods can be readily trained with structural data, in their current form it is not straightforward to train on binding data.…”
Section: Main Textmentioning
confidence: 99%